Baker cat - Simmonds, Posy. (London : Red Fox, 2005)
A cat, much abused by his owners, a baker and his wife, is too tired by day's end to catch any mice, but the mice soon come up with a plan to help the cat in exchange for being left alone.
Booklist.
6.9
K-3
Keywords: Bakers -- Fiction; Cats -- Fiction; Mice -- Fiction; Bakers -- Fiction; Cats -- Fiction; Mice -- Fiction